English, Arabic, and Chinese Loanwords in Brunei Malay - Balazs Huszka; Norazmie Yusof; Mohamed Mohiel-Din Ahmed; Tay Kok Jun (Talenta Publisher, 2021)
Brunei Malay is a unique Malay dialect spoken not only in Brunei Darussalam, but also in neighboring parts of Borneo. Although extensive data are available on lexical borrowings in Standard Malay and Indonesian, surprisingly, Brunei Malay has not been studied in this regard. Our paper aims to fill this gap by identifying English, Arabic and Chinese loanwords in the only available dictionary (Kamus Bahasa Melayu Brunei). We had looked into the linguistic distribution and word classes of the borrowed lexis, and understood that the main borrower was Arabic, followed by English; however, only a few words of Chinese origin could be found in the corpus. The most prominent word class was nouns, with a significantly lower number of verbs and adjectives. In the last part of our paper we are going to give some examples for usage of these loanwords in context.